Створення системи інформаційно-методичного забезпечення стратегічного планування - Шквиря, Наталя Олександрівна; Шквыря, Наталья Александровна; Shkvyria, Natalia (My University, 2017)
UK: Обґрунтовано необхідність створення спеціального центру підтримки стратегічного управління в системі галузевого стратегічного планування аграрних підприємств. Визначено завдання та напрямки роботи регіонального центру підтримки стратегічного управління. Запропоновано схему побудови інформаційно-аналітичної системи центру. EN: Formulation of the problem. To be competitive companies must implement a series of measures as part of a marketing plan. Particularly important issue of competitiveness in the strategic aspect in the changing internal and external environment. Results of the study. The essence and necessity of the strategic planning process is determined. The necessity of special center creation a for strategic management support in the system of agrarian enterprises strategic planning is substantiated. The problems faced by agricultural enterprises in strategic planning are investigated. The task of the center for strategic management support, namely, the carrying out of analytical work, the development of tools for strategic planning at enterprises, the construction of scenario forecasts for the industry, consultations, seminars, demonstration activities, as well as the publication and distribution of informational materials, etc. were developed. The most important task of the center is to collect objective information on the costs of production of the main types of agricultural products, as well as to develop an effective cost management tool. Such instruments include methods of controlling, adapted to the peculiarities of agricultural production, a system of sectoral norms, tied to local conditions, recommendations for the rational organization of centers of responsibility at enterprises, etc. The directions of work of the regional center for strategic management support are determined. The scheme of construction of the information-analytical center system is proposed. Conclusions. Thus, research has proved the need for the creation of a special strategic planning professionally engaged in the collection, storage, synthesis, processing and coordination of relevant strategic information, which could become a regional center for strategic management support, including a specialized information and analytical system.
Developing an information and methodological support system of strategic planning
Keywords: стратегічне планування; стратегічне управління; аграрні підприємства; зовнішнє середовище; регіональний центр підтримки стратегічного управління; strategic planning; strategic management; agrarian enterprises; external environment; regional center for strategic management support